Peningkatan Peran Usaha Kesehatan Sekolah di Sekolah Dasar Negeri Gisik Cemandi Sidoarjo - Rustam, Muh Zul Azhri; Susanti, Ari; Amalia, Nuke; Suhardiningsih, A.V. Sri; Riestiyowati, Maya Ayu; Amalin, Atika Mima; Rimbawa, H. A. Danang (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Student health center as a forum for providing Health Education for schoolchildren is expected to help improve the quality of education and achievement reflected in a healthy lifestyle and environment. Based on the observations made by the community service team, it is known that the implementation of the Student health center at SDN Gisik Cemandi is still straightforward due to limited funds, existing facilities, and infrastructure, and there is no form for recording and reporting Student health center activities. The purpose of this community service activity is to evaluate the activities of the student health center role at SDN Gisik Cemandi, Sedati, in Sidoarjo Regency. This community service activity was carried out on November 13-14th through small group discussions with the headmaster, teachers, and Student health center administrators at SDN Gisik Cemandi to identify needs in implementing the Student health center program. Based on the results of the cases found during the community service that had been carried out, the community service team made some products, namely: the form of a student health center service flow in the form of roller banners and videos as well as a student health center register book. The product is expected to improve the quality of Student health center services at SDN Gisik Cemandi.